Photocurable 3D Printing of High Toughness and Self‐Healing Hydrogels for Customized Wearable Flexible Sensors. (23rd September 2021) - Wu, Yuchao; Zeng, Yong; Chen, Yizhen; Li, Chao; Qiu, Renhui; Liu, Wendi
Abstract: Currently, most customized hydrogels can only be processed via extrusion‐based 3D printing techniques, which is limited by printing efficiency and resolution. Here, a simple strategy for the rapid fabrication of customized hydrogels using a photocurable 3D printing technique is presented. This technique has been rarely used because the presence of water increases the molecular distance between the polymer chains and reduces the monomer polymerization rate, resulting in the failure of rapid solid‐liquid separation during printing. Although adding cross‐linkers to printing inks can effectively accelerate 3D cross‐linked network formation, chemical cross‐linking may result in reduced toughness and self‐healing ability of the hydrogel. Therefore, an interpenetrated‐network hydrogel based on non‐covalent interactions is designed to form physical cross‐links, affording fast solid‐liquid separation. Poly(acrylic acid (AA)‐ N ‐vinyl‐2‐pyrrolidone (NVP)) and carboxymethyl cellulose (CMC) are cross‐linked via Zn 2+ ‐ligand coordination and hydrogen bonding; the resulting mixed AA‐NVP/CMC solution is used as the printing ink. The printed poly(AA‐NVP/CMC) hydrogel exhibited high tensile toughness (3.38 MJ m −3 ) and superior self‐healing ability (healed stress: 81%; healed strain: 91%). Some objects like manipulator are successfully customized by photocurable 3D printing using hydrogels with high toughness and complex structures. This high‐performance hydrogel has great potential for application in flexible wearable sensors. Abstract : This study proposes a universal photocuring 3D printing hydrogel strategy, focusing on the fabrication of hydrogels with high toughness and self‐healing ability for application in wearable sensors. An interpenetrated network hydrogel based on non‐covalent interactions is first designed to form physical cross‐links instead of the conventional covalent bonds to ensure printability of photocuring 3D printing.